Tolerances in Mechanisms - Husch, Julia; Walter, Michael S.J. (Research in Tolerancing, 2024)
The development of mechanisms is challenging due to the highly time-dependent key characteristics and the occurring random and systematic deviations. An integrated tolerance analysis-optimization-synthesis approach to cope with these challenges during the product development is presented. This approach is not limited to a pure functional tolerance analysis and optimization, in fact it also builds a bridge to economical evaluations and optimizations so that at the end a cost-optimal tolerance specification for a mechanism can be achieved. At the beginning of the chapter, the challenges related to mechanisms are highlighted, especially the time-dependent behavior of a mechanism during its operation and the different deviations occurring during the production and the operation of the mechanism. After that, the integrated approach for the statistical tolerance analysis of mechanisms is described, starting from the classic tolerance analysis of static assemblies and successively enlarging it to an integrated tolerance analysis approach for mechanisms taking into account different kinds of deviations. Based on the integrated analysis approach, the economical evaluation of the tolerance specification by the Walter-Hiller diagram, the functional and cost related optimization and the visualization by Tol/Mech—insight are presented. At the end, the applicability is demonstrated in a case stud